The influence of menstrual cycle on aerobic capacity - Łosień, Tomasz; Mędrak, Anna; Plaskacz, Paweł; Bajerska, Izabela; Reut, Magdalena; Dragon, Emilia; Polko, Martyna; Cebula, Aleksandra; Kuźma, Damian (Journal of Education, Health and Sport, 2018)
Introduction: Nowadays sociocultural changes that happen in highly developed countries increased the awareness of physical activity and healthy lifestyle. The social media have a significant influence on promoting the healthy lifestyle and motivating people to live fit. More and more women in their 20s take up physical activity to gain a beautiful body and feel healthy. Considering many hormones changes during the menstrual cycle, authors of many studies try to find direct link between the female menstrual cycle and aerobic capacity or general level of performance. The aims of the study: Does a phase of menstrual cycle affect physical capacity and reached submaximal level of heart rate? Does a phase of menstrual cycle affect aerobic capacity of the students? Does the subjective rate of physical capacity confirms in beep test result? Methods: 44 students of Medical University of Silesia took part in the study. Authorial questionnaire consisting of 13 questions was used to collect essential informations such as age, phase of the menstrual cycle, subjective rate of the aerobic capacity. Study group was measured with Beep test (a shuffle test used to assess aerobic performance, consisting of 21 levels that differ in the number of stages and the speed at which a distance of 20m should be covered in a given time). Before and after (1st and 5th minute) every run heart rate was measured with pulseoximeter. Results: Considering the beep test result sheets, the average of student’s results shows rather poor performance. (1) So far, the studies haven’t indicated any link between menstrual cycle and aerobic capacity (2) There is a relation between the frequency of training sessions and the aerobic capacity. Students that do an endurance training (in many forms) tend to have average/good beep test results